Pengaruh Civic Knowledge Terhadap Sikap Demokratis Peserta Didik SMA di Kabupaten Kuningan - Azhar, Muhammad Rabi; Sundawa, Dadang; Hadian, Vini Agustiani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to determine the effect of civic knowledge on the democratic attitude of senior high school students in Kuningan Regency. The research used a quantitative approach with a cross-sectional survey method. Data were collected through a test to measure civic knowledge and an attitude scale questionnaire to assess democratic attitudes. The sample consisted of 393 students selected using cluster sampling techniques. The results show that most students have a good level of civic knowledge and democratic attitudes. Based on simple linear regression analysis, civic knowledge has a significant effect on democratic attitudes, with a determination coefficient of 0.537. Thus, civic knowledge contributes 53.7% to the development of students’ democratic attitudes.